Incentives and obstacles to the development of innovative entrepreneurship in Ukraine - Kuzmenko, O.; Noskova, S. (Baltic International Academy, 2019)
Статтю присвячено висвітленню стимулів та перешкод розвитку інноваційного підприємництва в Україні. Досліджено економічні стимули. Визначено чинники позитивного та негативного впливу на розвиток інноваційного підприємництва в Україні. Розглянуто головні причини незадовільного стану інноваційної діяльності підприємств України. Адже потужним чинником та наймогутнішим стимулом до підвищення ефективності інноваційної підприємницької діяльності виступає економічна конкуренція. // The article is devoted to highlighting the incentives and obstacles to the development of innovative entrepreneurship in Ukraine. Economic incentives are studied. Factors of positive and negative influence on the development of innovative entrepreneurship in Ukraine are determined. The main reasons for the unsatisfactory state of innovation activity of Ukrainian enterprises are considered. After all, economic competition is a powerful factor and the most powerful incentive to increase the efficiency of innovative entrepreneurial activity.
Keywords: інноваційне підприємництво; стимули; чинники; innovative entrepreneurship; obstacles; incentives; factors